2021
DOI: 10.1007/s00125-021-05468-6
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immune circadian variation, synchronisation and possible dysrhythmia in established type 1 diabetes

Abstract: Aims/hypothesis The circadian clock influences both diabetes and immunity. Our goal in this study was to characterise more thoroughly the circadian patterns of immune cell populations and cytokines that are particularly relevant to the immune pathology of type 1 diabetes and thus fill in a current gap in our understanding of this disease. Methods Ten individuals with established type 1 diabetes (mean disease duration 11 years, age 18–40 years, six female) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Study subjects underwent clinical characterization (Tables S1 and S2) with their peripheral blood obtained during a morning blood draw to reduce circadian-related variation. 29 Peripheral blood immunophenotyping demonstrated the presence of granulocytosis (Figure 1A) with an increase in IL-1β + myeloid cells (CD15 + ; Figure 1B) in T1D subjects compared with controls. Increased circulating B-cells (CD19 + ; Figure 1C) and regulatory T cells (CD4 + CD25 + FoxP3 + ; Figure 1D), with a reduction in Th17 cells (CD4 + RORγt + ; Figure 1E) and an increase in gut-derived ILC1s (CD127 + CD161 + CD117 − CD294 − ) were also observed (Figure 1F) in T1D subjects compared with controls.…”
Section: Retinopathy Severity Correlates With Serum Markers Of Intest...mentioning
confidence: 97%
“…Study subjects underwent clinical characterization (Tables S1 and S2) with their peripheral blood obtained during a morning blood draw to reduce circadian-related variation. 29 Peripheral blood immunophenotyping demonstrated the presence of granulocytosis (Figure 1A) with an increase in IL-1β + myeloid cells (CD15 + ; Figure 1B) in T1D subjects compared with controls. Increased circulating B-cells (CD19 + ; Figure 1C) and regulatory T cells (CD4 + CD25 + FoxP3 + ; Figure 1D), with a reduction in Th17 cells (CD4 + RORγt + ; Figure 1E) and an increase in gut-derived ILC1s (CD127 + CD161 + CD117 − CD294 − ) were also observed (Figure 1F) in T1D subjects compared with controls.…”
Section: Retinopathy Severity Correlates With Serum Markers Of Intest...mentioning
confidence: 97%
“…These changes can be reversed by melatonin [ 57 , 58 ], highlighting the importance of pineal melatonin in the circadian optimization of pancreatic β-cell function. Circadian dysregulation is also intimately linked to a diverse array of T1DM symptomatology [ 59 ], including nocturnal non-dipping blood pressure increasing kidney disease [ 60 ], cardiac autonomic neuropathy [ 61 ], platelet morphology [ 62 ], microvascular complications [ 63 ], and patterned immune activity [ 64 ], whilst circadian variation in basal insulin requirement can be an early marker of autoimmune polyendocrine syndromes in T1DM [ 65 ]. Such data highlight the role of alterations in the circadian rhythm in T1DM pathophysiology.…”
Section: Wider T1dm Pathophysiologymentioning
confidence: 99%
“…Indeed, an animal study showed that TH17 cell differentiation follows the circadian clock 76 . Nevertheless, data on circadian rhythms of immune cells in MS are still very limited, in contrast to other autoimmune diseases such as type 1 diabetes, where phase shifts of 3–5 h in the circadian peak of blood levels have been demonstrated for B and T cells and their naive and effector memory subsets 77 . Circadian disruption might thus contribute to metabolic and immune cell dysregulation and malfunction in MS (Figure 2).…”
Section: Circadian Disturbances In Msmentioning
confidence: 99%